2016
DOI: 10.1002/tox.22375
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of in vitro effects of microcystin‐LR on intestinal epithelial cells

Abstract: The intestinal epithelium is a single-cell layer that provides an important barrier against natural toxins. Microcystin-LR (MC-LR), a cyclic heptapeptide, is one of the best known toxins able to alter the functions of intestine. This study evaluated the toxic effects and the possible mechanisms of MC-LR on barrier function of the intestinal epithelial cells. Intestinal epithelial cells (IEC-6) were exposed to 0, 6.25, 12.5, 25 and 50 μM MC-LR. Cell viability significantly decreased, while the ratio of apoptoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 39 publications
3
11
0
Order By: Relevance
“…After exposure of 0-50 μmol/L of MC-LR concentrations for 24 h in IEC-6 cells, the intracellular localization of MC-LR was in the cytoplasm and around the nucleus. Furthermore, western blot results revealed that there was a dose-dependent content following exposure to MC-LR[ 18 ].…”
Section: Concentration or Localization Of Mcs In The Small Intestinementioning
confidence: 99%
See 1 more Smart Citation
“…After exposure of 0-50 μmol/L of MC-LR concentrations for 24 h in IEC-6 cells, the intracellular localization of MC-LR was in the cytoplasm and around the nucleus. Furthermore, western blot results revealed that there was a dose-dependent content following exposure to MC-LR[ 18 ].…”
Section: Concentration or Localization Of Mcs In The Small Intestinementioning
confidence: 99%
“…Previous studies indicated that MCs can be transported across enterocyte membranes via OATPs[ 2 ]. Moreover, studies have manifested that cell viability significantly decreased, while the ratio of apoptotic cells increased, after intestinal epithelial cells (IEC-6) and human intestinal Caco-2 cells were exposed to MCs[ 18 ]. MCs can affect the integrity of the intestinal barrier by decreasing its transepithelial electrical resistance (TEER) values and inducing the cytoskeletal protein expression of occludin and ZO-1 in IECs in a dose-dependent decrease[ 18 ].…”
Section: Pathological Effect Of Mcs In the Intestinesmentioning
confidence: 99%
“…3 Recent studies demonstrate that MC-LR has toxic effect on the intestine. 4 However, the mechanism of this phenomenon is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…These cells have microvilli, centrioles, Golgi complexes, and junctional complexes according to an ultrastructural study ( Quaroni et al, 1979 ). Due to the characteristics of IEC-6 cells, this cell line has also been used in studies of hepatotoxicity ( Zhou et al, 2017 ), tight junctions ( Yu et al, 2016 ) and TRP channels ( Kono et al, 2013 ; Yamawaki et al, 2014 ). Cells were transiently transfected with plasmid to produce TRPV1- overexpressing and TRPV1-knockdown cells.…”
Section: Discussionmentioning
confidence: 99%